Rekonstruksi, Keladillan, Pollil Rekonstruksi Keadilan Poligami Dalam Hukum Perkawinan Islam Di Indonesia : Rekonstruksi Keadilan Poligami Dalam Hukum Perkawinan Islam Di Indonesia - Mas adah, Mas adah; A'la, Abd (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2025)
Polygamy is a classic issue but is still interesting to study. The basis used is QS an Nisa verse 3. According to Musdah, this verse talks about how to provide protection for orphans. Even if polygamy is practiced, it is one breath with the protection of orphans. Therefore, the law of polygamy is haram lighayrih because the condition of its permissibility is justice which includes material and immaterial is very difficult to achieve. The prohibition of polygamy because of justice to his wives becomes the legal illat. The Marriage Law in Indonesia in regulating polygamy does not seem to be fair to women and views women as sub ordinate. While Musdah's thinking about polygamy in positive law in Indonesia is Article 3 paragraph (1) of Law No.1 of 1974 reads "Basically in a marriage a man can only have one wife. However, on the other hand, it provides a loophole for polygamy, even a maximum of four wives. This permission contains inconsistencies, because on the one hand it confirms the principle of monogamy but on the other hand it gives leeway to husbands to polygamy even though it is limited to four wives with several reasons but all the reasons for allowing polygamy are in favor of the husband's interests without considering the interests of the wife. It appears that the wife is an object to be polygamized and the inconsistency where the principle of marriage is monogamous but still provides a loophole for polygamy. This research aims to analyze Musdah Mulia's thoughts on polygamy justice in Islamic law and positive law in Indonesia. The method used by the author in writing is descriptive normative legal research method, the result of this research analysis is a critical study analysis of Siti Musdah Mulia's thoughts on polygamy justice in Islamic law and positive law in Indonesia